One + one = blue - Auch, Mary Jane (New York : Henry Holt and Company, 2013)
Branded the class loser, twelve-year-old Basil reluctantly becomes friends with a bossy new girl who, like Basil, has synesthesia and comes to Basil's aid when his estranged mother returns and turns his life upside down.
Keywords: Synesthesia -- Fiction; Psychological fiction